In Their Own Words: Student Narratives of Intercultural Engagement, Barriers, and Impact at a Canadian University - Jiang, Yujie; Garson, Kyra; McLean, Amie; Hoare, Alana; Virani, Anila; Harasymchuk, Brad (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2025)
⁠⁠⁠⁠⁠⁠⁠Enhancing and evaluating intercultural learning in Canadian postsecondary education is increasingly important in the context of domestic student diversity, the rapid internationalization of higher education, and collective responsibilities to address the local and global implications of colonialism at relational, institutional, and systemic levels. This paper provides the findings of qualitative research designed to explore student perspectives on their intercultural attitudes, knowledges, and skills, as well as to identify whether and how their learning resulted in intercultural praxis. Data from a student survey coded and thematically analyzed revealed a variety of themes of interest to educators. The findings highlight the need to address individual and institutional barriers to intercultural learning, while acknowledging that societal barriers also constrict the advancement of inclusion and diversity goals. Key areas for improvement include moving beyond deficit models of cultural diversity; enhancing pedagogical supports and professional development in intercultural praxis; and progressing past superficial or individualistic approaches in ways that empower students to apply their intercultural knowledges and skills through transformative actions that gesture towards socially just futures.